2021
DOI: 10.1002/ange.202017025
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Evidence for the Promotional Effect of Acid Sites on the Diffusion of Alkenes through Small‐Pore Zeolites

Abstract: The diffusion of saturated and unsaturated hydrocarbons is of fundamental importance for many zeolitecatalyzedprocesses.T ransport of small alkenes in the confined zeolite pores can become hindered, resulting in as ignificant impact on the ultimate product selectivity and separation. Herein, intracrystalline light olefin/paraffin diffusion through the 8-ring windows of zeolite SAPO-34 is characterized by ac omplementary set of first-principle molecular dynamics simulations,PFG-NMR experiments,and pulse-respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…The recent advances in modeling/imaging techniques also allows one to obtain a better understanding of a heterogeneous catalytic process, from different length and time scales. ,, For example, the use of APT clearly reveals the relationship between coke species and Brønsted acid sites distribution, and it is found that the aluminum-rich surface of ZSM-5 crystals accommodate more coke species . As to the MTA catalyst, which has both Lewis acidic metals and Brønsted acid sites, however, the spatial relationship between different acid sites and coke is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent advances in modeling/imaging techniques also allows one to obtain a better understanding of a heterogeneous catalytic process, from different length and time scales. ,, For example, the use of APT clearly reveals the relationship between coke species and Brønsted acid sites distribution, and it is found that the aluminum-rich surface of ZSM-5 crystals accommodate more coke species . As to the MTA catalyst, which has both Lewis acidic metals and Brønsted acid sites, however, the spatial relationship between different acid sites and coke is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is essential to apply advanced spatial-resolved imaging techniques to disclose such a relation, which facilitates designing better coking-resistant MTA catalysts. Besides, the simulation advances also provide in-depth theoretical understandings for the MTH chemistry. Based on small-pore zeolite, enhanced sampling molecular dynamics simulations indicate that the diffusion of light olefins is manipulated by many factors, among which the presence of Brønsted acid sites in the 8-ring enhances the diffusion process . As for the MTA catalysts, the factors affecting the diffusion properties of various species such as the light olefins and aromatics, still need to be illuminated theoretically.…”
Section: Discussionmentioning
confidence: 99%
“…To uncover the effect of acidity and adsorbate loading on the transport mechanism behind the diffusion of paraffins and olefins, the dynamic properties of ethene, ethane, propene and propane inserted in H-SAPO-34 have been investigated using Pulsed-field gradient (PFG) NMR analysis together with ab initio MD (AIMD) and ab initio umbrella sampling (AI-US) modelling techniques. 216 The umbrella sampling technique was employed to determine the free energy profile of diffusion through the 8 membered ring (8MR) windows of the H-SAPO-34 zeolite, having 1-3 adsorbates and 0-2 Brønsted acid sites per unit cell. The increase in adsorbate loading from one to three molecules per cage led to a slightly enhanced self-diffusion rate of ethene, while ethane mobility decreased.…”
Section: Diffusion and Mobility Of Species During The Mto Processmentioning
confidence: 99%
“…1 H PFG NMR analysis at room temperature provided further evidence that the diffusion coefficient (D) of ethene is directly proportional to Brønsted acid site (BAS) density, as D E 10 À11 m 2 s À1 at BAS = 0.65 mmol g À1 goes to D E 2 Â 10 À11 m 2 s À1 at BAS = 1.13 mmol g À1 . 216 The improved diffusion profile of alkenes at higher BAS density is attributed to the polarization induced by the BAS on the adsorbed olefins creating an electrostatic field in the proximity of the 8MR, which leads to a flatter free energy surface that facilitates the transition from one cage to another. Supportive evidence has been found in the formation of alkene p-H complexes, detected at 3307 cm À1 by FT-IR measurements.…”
Section: Diffusion and Mobility Of Species During The Mto Processmentioning
confidence: 99%
See 1 more Smart Citation